Implementation of Educative Recreative Architecture on Children's Library in Banda Aceh - siti shara (Universitas Syiah Kuala, 2019)
Indonesia is one of the country that has low interest in reading, even though we all know it has something to do in a person’s intelligence. To increase the interest in reading, it has to be started by introducing books since earlier age. Children needs to know about books more often to increase their interest in reading. It need some facilities to make it happen, such as libraries for children. This library has to match with the character of children that loves to play. Therefore, entertaining and educating theme fits well to this library. This theme provides entertaining facilities such as playground, story-telling, perform stage, etc. with these facilities, hopefully will create a fun situation while studying.Keywords: entertaining, educating, children’s library.